MARINE FISH LANDINGS IN INDIA — ESTIMATES AND PRECISION - Alagaraja, K; Srinath, M (Indian Journal of Fisheries, 2011)
The reliabdlity of estimates of marine fish production arrived at by theCentral Marine Fisheries Research Institute based on the stratified multistagerandom sampling is further proved by tesiting the same, by fitting regressiion equations,with the export figures released by the Marine Products Export DevelopmentAuthority